Equitable access to cancer patient pathways in Norway - a national registry-based study - Frank Olsen; Bjarne K. Jacobsen; Ivar Heuch; Kjell M. Tveit; Lise Balteskard (BMC, 2021)
Abstract Background In 2015, cancer patient pathways (CPP) were implemented in Norway to reduce unnecessary non-medical delay in the diagnostic process and start of treatment. The main aim of this study was to investigate the equality in access to CPPs for patients with either lung, colorectal, breast or prostate cancer in Norway. Methods National population-based data on individual level from 2015 to 2017 were used to study two proportions; i) patients in CPPs without the cancer diagnosis, and ii) cancer patients included in CPPs. Logistic regression was applied to examine the associations between these proportions and place of residence (hospital referral area), age, education, income, comorbidity and travel time to hospital. Results Age and place of residence were the two most important factors for describing the variation in proportions. For the CPP patients, inconsistent differences were found for income and education, while for the cancer patients the probability of being included in a CPP increased with income. Conclusions The age effect can be related to both the increasing risk of cancer and increasing number of GP and hospital contacts with age. The non-systematic results for CPP patients according to income and education can be interpreted as equitable access, as opposed to the systematic differences found among cancer patients in different income groups. The inequalities between income groups among cancer patients and the inequalities based on the patients' place of residence, for both CPP and cancer patients, are unwarranted and need to be addressed.